The German minorities in Central and Eastern Europe and the Germanization policy in Warthegau 1939-1945 = Mniejszości niemieckie z Europy Środkowej i Wschodniej w polityce germanizacji kraju Warty (1939-1945) - Kiec, Olgierd (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the Second World War, the Western part of the occupied Poland was incorporated directly into the Third Reich as Reichsgau Danzig-Westpreussen, Reichsgau Wartheland (with the main city Posen/Poznań), Regierungsbezirk Kattowitz (part of the Provinz Schlesien) and Regierungsbezirk Zichenau (Ciechanów, part of the Provinz Ostpreussen). The most radical efforts for the creation of the new German society were implemented in Reichsgau Wartheland, an administration unit founded from the parts of former Prussian (until 1918) Provinz Posen as well as former Russian-Poland with the large industrial city Lodz.
Keywords: German East; German minorities in Europe German occupation policy in Poland 1939-1945; ethnic cleansing in Europe; Niemiecki Wschód; mniejszości niemieckie w Europie niemiecka polityka okupacyjna w Polsce 1939-1945; czystki etniczne w Europie